BRICS COUNTRIES’ POLITICAL AND LEGAL PARTICIPATION IN THE GLOBAL CLIMATE CHANGE AGENDA - E. Gladun; D. Ahsan (BRICS Law Journal, 2016)
The article presents an overview and analysis of international legal regulations on climate change. The authors examine how the international regime related to climate change has evolved in multilateral agreements. A special focus is put on the principle of common but differentiated responsibilities which became the basis of discord among states in discussing targets and responsibilities in climate change mitigation. The authors note that in 2015 the international climate change regime entered a new stage where the most important role is determined for developing countries, both in the legal and in the financial infrastructure, and in the formation of an international climate change policy.The importance of the participation of Brazil, Russia, India, China, and South Africa (BRICS) in an international climate change regime has been recognized for some time. The article describes the policy and regulations on climate-related issues in BRICS. The authors compare the key actions and measures BRICS have taken for complying with international climate change documents. They highlight that global climate change action cannot be successful without BRICS countries’ involvement. BRICS must therefore make adequate efforts in emissions reduction measures and significant commitments in respect of the international climate change regime. The authors propose three major steps for BRICS to take the lead in dealing with climate change. First, BRICS need to foster further discussion and cooperation on climate issues and work out an obligatory legal framework to fight climate change collectively as well as unified legislation at their domestic levels. Second, Russia and other BRICS countries have the potential to cooperate in the field of renewable energy through the exchange of technology, investment in the sector, and the participation of their energy companies in each other’s domestic market. Assuming Russia will support the development and enhancement of renewable technologies in BRICS countries, it can take a leadership position in the group. Third, in the international process of tackling climate-related issues BRICS should act as a bloc. Russia’s distancing itself from its partners is considered a deficiency in strengthening the BRICS countries’ role in global governance. BRICS are capable of serving as a vigorous platform in driving climate change negotiations leading to effective binding regulations in 2020–2030 and, provided that the countries cooperate successfully, BRICS will carry the combined weight of the entire group in the global arena.